Case Report: ST-Elevation Myocardial Infarction Secondary to Acute Atherothrombotic Occlusion Treated With No Stent Strategy - Dhawan, Rahul; Samant, Saurabhi; Gajanan, Ganesh; Chatzizisis, Yiannis S. (Frontiers in Cardiovascular Medicine, 2022)
Background: Intravascular imaging plays a vital role in pathophysiology-based diagnosis and treatment of patients with ST elevation myocardial infarction (STEMI). We present a case of STEMI due to plaque erosion, which was managed with a no stent approach. Case Summary: A 43-years-old female with a history of tobacco abuse presented with an anterior STEMI. Coronary angiography revealed acute thrombotic occlusion of the left anterior descending artery with spontaneous recanalization.. Intravascular imaging with optical coherence tomography (OCT) demonstrated plaque erosion as the underlying etiology for the acute thrombotic occlusion. A no stent strategy with aspiration thrombectomy and dual anti-platelet therapy was used to manage the patient given that there was no evidence of plaque rupture. Repeat coronary imaging was done at 2-month and 27-month follow-up to assess the status of the lesion. Conclusion: A 43-years-old female with STEMI due to plaque erosion was successfully managed only by thrombus aspiration and not by angioplasty and stent placement. Individualized treatment approach in patients with acute coronary syndromes, can not only achieve optimal management goals, but also avoid unnecessary complications associated with interventions. This case illustrates how intracoronary imaging and pathophysiology guided treatment can dramatically change management. In this young patient STEMI was managed purely by thrombus aspiration. Intravascular imaging obviated the need for stent placement possibly preventing stent related complications including restenosis and thrombosis.